1991
DOI: 10.1099/0022-1317-72-4-809
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor- , interferon-  and interferon-beta exert antiviral activity in nervous tissue cells

Abstract: The individual and synergistic antiviral effects of cytokines released by infiltrating immune cells or by cells of the nervous system may play an important role in inhibiting virus spread during infections of the central nervous system (CNS). We examined the antiviral activity against the neurotropic pseudorabies virus (PRV) of interferon-y (IFN-y) and tumour necrosis factor-~ (TNF-ct), and combinations of these cytokines, as compared to that of IFN-fl, in rat nervous tissue cells. PRV replicated efficiently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Consistent with the hypothesis that abrogation of the ability to induce the TNF/IFNβ synergistic state is a prerequisite for cellular immortalization and/or transformation, all previous reports describing TNF/IFNβ synergistic responses have been performed only in primary cells, such as human macrophages [10], human fibroblasts [8,11], or rat neuronal cells [12]. Interestingly, there is a large body of literature demonstrating that TNF can also synergize with IFNγ, but this synergistic state is demonstrably different from that induced by TNF plus type I IFN [13].…”
Section: Discussionmentioning
confidence: 79%
“…Consistent with the hypothesis that abrogation of the ability to induce the TNF/IFNβ synergistic state is a prerequisite for cellular immortalization and/or transformation, all previous reports describing TNF/IFNβ synergistic responses have been performed only in primary cells, such as human macrophages [10], human fibroblasts [8,11], or rat neuronal cells [12]. Interestingly, there is a large body of literature demonstrating that TNF can also synergize with IFNγ, but this synergistic state is demonstrably different from that induced by TNF plus type I IFN [13].…”
Section: Discussionmentioning
confidence: 79%
“…MHC class II restricted T-cells, may also be involved in the cytotoxic response which restricts viral replication [36]. Moreover, these CD4 + T-cells may inhibit viral replication by production of cytokines with antiviral activity, such as IFN-g [37]. CD4 + T-cells have been implicated in the resistance against another alphaherpes virus, herpes simplex virus (HSV); Manickan et al [7] demonstrated that in mice immunized with HSV-gB DNA, a CD4 + T-cell response protected the animals from infection with HSV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Among DNA viruses~ adenovirus (Wong et al, 1986;Mayer et al, 1992), African swine fever virus (Esparza et al, 1988), and the alphaherpesviruses HSV (Wong et al, 1986;Feduchi et al, 1989) and pseudorabies virus (Schijns et al, 1991) have been found to be susceptible to this combination of cytokines. Here we report that the replication of MCMV, a betaherpesvirus, is also susceptible to their synergistic action.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility, not mutually exclusive of the former, is that IFNp must associate with other cytokines to exhibit a direct antiviral effect. It has been reported that turnout necrosis factor (TNF) and IFN-~ in combination have synergistic antiviral activity against DNA viruses such as adenovirus type 2 (Mayer et al, 1992;Wong & Goeddel, 1986), herpes simplex virus type 1 (HSV-1) (Feduchi et al, 1989) and HSV-2 (Wong & Goeddel, 1986) and pseudorabies virus (Schijns et al, 1991). The TNFs 0~ and fl (TNF-~/fl) are synthesized by monocytes and lymphocytes respectively, bind to the same receptor and have indistinguishable biologica/ activities (Aggarwal et al, 1985;Beutler & Cerami, 1989;Paul & Ruddle, 1988).…”
Section: Introductionmentioning
confidence: 99%